2005
DOI: 10.1111/j.1523-1755.2005.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystals cause acute necrotic cell death in renal proximal tubule cells, but not in collecting tubule cells

Abstract: This study shows that calcium oxalate crystals cause acute inflammation-mediated necrotic cell death in renal proximal tubular cells, but not in collecting tubule cells. The crystal-induced generation of reactive oxygen species by renal tubular cells is a general response to tissue damage and the increased levels of DNA synthesis seem to reflect regeneration rather than growth stimulation. As long as the renal collecting ducts are not obstructed with crystals, these results do not support an important role for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 35 publications
7
71
0
1
Order By: Relevance
“…A variety of renal epithelial cells including LLC-PK 1 , MDCK, HK-2 (human kidney), NRK (normal rat kidney) and RPTEC (human renal proximal tubular epithelial cells), when exposed to high levels of oxalate, or brushite or CaOx crystals, show signs of membrane damage, and release LDH and enzymes such as γ-glutamyl trasnspeptidase, and N-acetyl-β-glucoseaminidase (4,6,12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of renal epithelial cells including LLC-PK 1 , MDCK, HK-2 (human kidney), NRK (normal rat kidney) and RPTEC (human renal proximal tubular epithelial cells), when exposed to high levels of oxalate, or brushite or CaOx crystals, show signs of membrane damage, and release LDH and enzymes such as γ-glutamyl trasnspeptidase, and N-acetyl-β-glucoseaminidase (4,6,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we also examined the production of hydrogen peroxide (H 2 O 2 ), one of the reactive oxygen species (ROS), and 8-isoprostane (8-IP), a marker for oxidative stress. Since renal epithelial cells exposed to CaOx crystals produce significant amounts of inflammatory mediators, monocyte chemoattractant protein-1 (MCP-1) (4) and prostaglandin-E2 (PGE2) (5,12) by the exposed cells we also investigated their production. As mentioned above, Randall's plaques start in the basement membrane and renal interstitium resulting in the tubular epithelial exposure from the basal side.…”
Section: Introductionmentioning
confidence: 99%
“…8 COM crystals could modify the membrane structure and function, activate ROS, cause oxidant/antioxidant imbalance, lead to mitochondrial dysfunction, and increase lipid peroxidation, 19 which induces apoptotic or necrotic cell death in renal epithelial cells. 9,[47][48][49] COD is the second most common component of CaOx renal stones, although existing studies on the toxic effect of COD crystals on renal epithelial cells are inadequate. Our previous study reported that nano-COD induced higher toxicity on Vero cells compared with the micro-sized crystals.…”
Section: Discussionmentioning
confidence: 99%
“…COM crystal-cell interaction leads to production of reactive oxygen species (ROS), for example, superoxide (O 2 ?À ) 24 and H 2 O 2 . 25 These ROS products can mediate proinflammatory cytokines, for example, monocyte chemoattractant protein-1, leading to inflammation, epithelial cell injury and ultimately necrotic cell death. 26,27 Nevertheless, pathogenic mechanisms underlying kidney stone formation remain unclear.…”
mentioning
confidence: 99%